Dietary Fatty Acids in Postprandial Triglyceride-Rich Lipoproteins Modulate Human Monocyte-Derived Dendritic Cell Maturation and Activation - Carlos Vazquez-Madrigal (Nutrients, 2020)
Dietary fatty acids have been demonstrated to modulate systemic inflammation and induce the postprandial inflammatory response of circulating immune cells. We hypothesized that postprandial triglyceride-rich lipoproteins (TRLs) may have acute effects on immunometabolic homeostasis by modulating dendritic cells (DCs), sentinels of the immunity that link innate and adaptive immune systems. In healthy volunteers, saturated fatty acid (SFA)-enriched meal raised serum levels of granulocyte/macrophage colony-stimulating factor GM-CSF (SFAs > monounsaturated fatty acids (MUFAs) = polyunsaturated fatty acids (PUFAs)) in the postprandial period. Autologous TRL-SFAs upregulated the gene expression of DC maturation (CD123 and CCR7) and DC pro-inflammatory activation (CD80 and CD86) genes while downregulating tolerogenic genes (PD-L1 and PD-L2) in human monocyte-derived DCs (moDCs). These effects were reversed with oleic acid-enriched TRLs. Moreover, postprandial SFAs raised IL-12p70 levels, while TRL-MUFAs and TRL-PUFAs increased IL-10 levels in serum of healthy volunteers and in the medium of TRL-treated moDCs. In conclusion, postprandial TRLs are metabolic entities with DC-related tolerogenic activity, and this function is linked to the type of dietary fat in the meal. This study shows that the intake of meals enriched in MUFAs from olive oil, when compared with meals enriched in SFAs, prevents the postprandial production and priming of circulating pro-inflammatory DCs, and promotes tolerogenic response in healthy subjects. However, functional assays with moDCs generated in the presence of different fatty acids and T cells could increase the knowledge of postprandial TRLs’ effects on DC differentiation and function.